Magnetic Analysis of Modified-Rotor Switched Reluctance Motor - KAKİLLİ, ADNAN (KAUNAS UNIV TECHNOLOGY, 2011)
A. Kakilli. Magnetic Analysis of Modified-Rotor Switched Reluctance Motor // Electronics and Electrical Engineering. Kaunas: Technologija, 2011. - No. 9(115). - P. 21-26. In this study magnetic analyses of a 3-phase, 12/8-pole, modified-rotor switched reluctance motor have been made. For this purpose, this motor has been modeled distorting 3.6 degrees by using a rotor helical method having a right geometry in 3-D environment, using the finite element method with Ansoft-Maxwell 3D, magnetic analyses of it have been made. The results of this analysis have been compared with the results calculated by analytical methods. The results obtained through the studies have been given modally. III. 12, bibl. 13, tabl. 2 (in English; abstracts in English and Lithuanian).